The theoretical and practical value of english lexicology - Akhrorova Dildora; SattorovaYulduz (FILOLOGIYA UFQLARI JURNALI, 2022)
This article gives information about both theoretical and practical value of english lexicology and also its own main aims. Modern English lexicology investigates the problem of word structure and word formation the classification of vocabulary unit, description of the relations between different lexical layers of English vocabulary.